Cytokinin oxidase/dehydrogenase overexpression modifies antioxidant defense against heat, drought and their combination in Nicotiana tabacum plants - Lubovská, Zuzana; Dobrá, Jana; Storchová, Helena; Wilhelmová, Naďa; Vanková, Radomíra (Journal of plant physiology, 2014)
Cytokinins (CKs) as well as the antioxidant enzyme system (AES) play important roles in plant stress responses. The expression and activity of antioxidant enzymes (AE) were determined in drought, heat and combination of both stresses, comparing the response of tobacco plants overexpressing the main cytokinin degrading enzyme, cytokinin oxidase/dehydrogenase, under the control of root-specific WRKY6 promoter (W6:CKX1 plants) or constitutive promoter (35S:CKX1 plants) and the corresponding wild-type (WT). Expression levels as well as activities of cytosolic ascorbate peroxidase, catalase 3, and cytosolic superoxide dismutase were low under optimal conditions and increased after heat and combined stress in all genotypes. Unlike catalase 3, two other peroxisomal enzymes, catalase 1 and catalase 2, were transcribed extensively under control conditions. Heat stress, in contrast to drought or combined stress, increased catalase 1 and reduced catalase 2 expression in WT and W6:CKX1 plants. In 35S:CKX1, catalase 1 expression was enhanced by heat or drought, but not under combined stress conditions. Mitochondrial superoxide dismutase expression was generally higher in 35S:CKX1 plants than in WT. Genes encoding for chloroplastic AEs, stromatal ascorbate peroxidase, thylakoidal ascorbate peroxidase and chloroplastic superoxide dismutase, were strongly transcribed under control conditions. All stresses down-regulated their expression in WT and W6:CKX1, whereas more stress-tolerant 35S:CKX1 plants maintained high expression during drought and heat. The achieved data show that the effect of down-regulation of CK levels on AES may be mediated by altered habit, resulting in improved stress tolerance, which is associated with diminished stress impact on photosynthesis, and changes in source/sink relations.
Keywords: proteiny huseníčku; listy rostlin; down regulace; Ascorbate Peroxidases; antioxidancia; Oxidoreductases; fotosyntéza; Arabidopsis; Photosynthesis; Droughts; Plant Roots; Cytokinin; Arabidopsis Proteins; promotorové oblasti (genetika); oxidoreduktasy; tabák; Models, Biological; Cytokinins; regulace genové exprese u rostlin; Stress, Physiological; kořeny rostlin; Catalase; cytokininy; Plants, Genetically Modified; Drought; Down-Regulation; Nicotiana; biologické modely; Antioxidants; Gene Expression Regulation, Plant; katalasa; vysoká teplota; Plant Leaves; Promoter Regions, Genetic; geneticky modifikované rostliny; askorbátperoxidasa; Heat; Superoxide Dismutase; fyziologický stres; superoxiddismutasa; Hot Temperature; Antioxidant enzymes; období sucha